FOREIGN EXPERIENCE IN THE FORMATION OF INTER-BUDGETARY RELATIONS - Perneev, Даурен Хамитович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
The article runs about the formation of foreign experience of interbudget relations. Author presents a comparative analysis of the main types of models of inter-budgetary relations, ascertain the characteristics of each of the models and he generalizes the experience of building interbudgetary relations between unitary states.